Los objetivos de la instrucción gramatical en la enseñanza del español como lengua materna - Sánchez Avendaño, Carlos (2007)
In the following article, the value related to Spanish grammar teaching as a first language within Costa Rican secondary education is examined through the analysis of the 2005 curriculum and opinions of future teachers. Moreover, the grammatical framework for such traditional education is reviewed and a functional approach is proposed as an alternative to introduce grammar in class. Lastly, five objectives for grammar teaching are outlined.